Atorvastatin Restores PPARα Inhibition of Lipid Metabolism Disorders by Downregulating miR-21 Expression to Improve Mitochondrial Function and Alleviate Diabetic Nephropathy Progression - Xiang, Jiayi; Zhang, Huifang; Zhou, Xingcheng; Wang, Dan; Chen, Rongyu; Tan, Wanlin; Liang, Luqun; Shi, Mingjun; Zhang, Fan; Xiao, Ying; Zhou, Yuxia; Wang, Yuanyuan; et al. (Frontiers in Pharmacology, 2022)
Atorvastatin is a classical lipid-lowering drug. It has been reported to have renoprotective effects, such as reducing urinary protein excretion and extracellular matrix aggregation. The present study aimed to investigate the specific mechanism of action of Atorvastatin in type 1 diabetic mice(T1DM) in inhibiting renal tubular epithelial cell injury following treatment with high glucose and high fat. The anti-injury mechanism of Atorvastatin involved the inhibition of miR-21 expression and the upregulation of the transcription and expression of its downstream gene Peroxisome proliferator-activated receptors-α(PPARα). An increase in blood glucose and lipid levels was noted in the T1DM model, which was associated with renal fibrosis and inflammation. These changes were accompanied by increased miR-21 levels, downregulation of PPARα and Mfn1 expressions, and upregulation of Drp1 and IL6 expressions in renal tissues. These phenomena were reversed following the administration of Atorvastatin. miR-21 targeted PPARα by inhibiting its mRNA translation. Inhibition of miR-21 expression or Fenofibrate(PPARα agonist) administration prevented the decrease of PPARα in renal tubular epithelial cells under high glucose(HG) and high fat(Palmitic acid, PA) conditions, alleviating lipid metabolism disorders and reducing mitochondrial dynamics and inflammation. Consistent with the in vivo results, the in vitro findings also demonstrated that mRTECs administered with Atorvastatin in HG+PA increased PPARα expression and restored the normal expression of Mfn1 and Drp1, and effectively increasing the number of biologically active mitochondria and ATP content, reducing ROS production, and restoring mitochondrial membrane potential following Atorvastatin intervention. In addition, these effects were noted to the inhibition of FN expression and tubular cell inflammatory response; however, in the presence of miR-21mimics, the aforementioned effects of Atorvastatin were significantly diminished. Based on these observations, we conclude that Atorvastatin inhibits tubular epithelial cell injury in T1DM with concomitant induction of lipid metabolism disorders by a mechanism involving inhibition of miR-21 expression and consequent upregulation of PPARα expression. Moreover, Atorvastatin regulated lipid metabolism homeostasis and PPARα to restore mitochondrial function. The results emphasize the potential of Atorvastatin to exhibit lipid-regulating functions and non-lipid effects that balance mitochondrial dynamics.